Synthesis of the algorithm for the flow parameters optimal control of the reversible conveyor - Pihnastyi, O. M.; Ivanovska, O. V.; Sobol, Maksym (Національний університет "Запорізька політехніка", 2022)
The problem of optimal control of flow parameters of a conveyor-type transport system containing sections with reversible conveyors is considered. The object of the stady was an analytical model of a reversible transport conveyor for synthesizing an algorithm for optimal control of the flow parameters of a reversible transport conveyor. The goal of the work is to develop a synthesis technique for an algorithm for optimal control of the flow parameters of a reversible transport conveyor based on an analytical model of a conveyor section containing a transport delay. An analytical model of a reversible conveyor has been developed for the case of a constant speed of a conveyor belt, which makes it possible to determine the values of the output flows from the reverse section with known values of material flows coming to the input of the conveyor section. To build a model of the reversible section of the conveyor, an analytical model of the section of the conveyor in partial derivatives, containing the transport delay, was used. When constructing the model, the assumption was made about the instantaneous switching of the direction of movement of the conveyor belt, and it is also assumed that the interval between switching the direction of the belt speed exceeds the values of the transport delay for the conveyor section. To synthesize an algorithm for optimal control of the reversible conveyor, a control quality criterion was introduced. The formulation of the problem of optimal control of the flow parameters of the reversible conveyor is given, based on the Pontryagin maximum principle. The Hamilton function for the controlled system is written, taking into account the criterion of the quality of control of the reversible conveyor. A technique for synthesizing an algorithm for optimal control of the material output flow of a section of a reversible conveyor is demonstrated. The conditions for switching the direction of the speed of the conveyor belt are determined. The developed model of the reversible conveyor section is used to synthesize an algorithm for optimal control of the material output flow of the reversible conveyor section. A method for the synthesis of algorithms for optimal control of the flow parameters of a transport system with sections containing reversible conveyors has been developed. The construction of an analytical model opens up new perspectives for the design of transport conveyor control algorithms, which can be used to reduce the specific energy costs for material transportation in the mining industry.
Синтез алгоритму оптимального управління поточними параметрами реверсивного конвеєра
Keywords: reversible conveyor; PiKh-conveyor model; transport delay; conveyor belt speed; transport system; conveyor control; PiKh-модель конвеєра; транспортна затримка; швидкість стрічки конвеєра; транспортна система; керування конвеєром; реверсивний конвеєр